Pengaruh Strategi Penetapan Harga, Promosi, Dan Lokasi Dalam Meningkatkan Minat Beli Pelanggan Tabung Gas 12 Kg Pada PT. Jalahan Arta Prima Rantauprapat - Sa’baniah, Nina (Universitas Labuhanbatu, 2021)
This study aims to determine the price, promotion, and location in increasing customer buying interest gas cylinder 12 Kg at PT. Arta Prima Rantauprapat. The population in this study are consumers who purchase LPG cylinders 12 Kg at PT. Jalan Arta Prima Rantauprapat is as many as 408 people. This study uses a simple random sampling method that is where random withdrawal by providing equal opportunities for each member of the population to eliminate his opinion. We are a company engaged in the procurement of goods and services industry. The prices offered by this company are as follows: the prices offered by this company are as follows: the prices offered by this company are as follows: the prices offered by this company are as follows: the prices offered by this company are as follows: the prices offered by this company are by this company are the prices offered by this company are the prices offered by this company are the prices offered by the company.Â Â In the variable promotion and location and significant influence on buying interest in filling LPG cylinders 12 Kg at PT. Arta Prima Rantauprapat. R Square value of 0.318 or 31.8% buying interest can be converted by price penetration, promotion and location while the side 68.2% can be converted by other variables that are not shared in this study. SPSS (Social Science Statistics package) software version 22.Â